Cotreatment of Small Gold Nanoparticles Protects Against the Increase in Cerebral Acetylcholinesterase Activity and Oxidative Stress Induced by Acute Ethanol Exposure in the Zebrafish. (1st March 2021) - Torres, Carolina Antunes; Mendes, Niuany Viel; Baldin, Samira Leila; Bernardo, Henrique Teza; Vieira, Karine Medeiros; Scussel, Rahisa; de Bem Silveira, Gustavo; Silveira, Paulo Cesar Lock; Machado-de-Ávila, Ricardo Andrez; Rico, Eduardo Pacheco
Highlights: Gold nanoparticles protect acetylcholinesterase activity in zebrafish brain. Gold nanoparticles alters oxidative stress in the zebrafish brain. Oxidative stress induced by ethanol is regulated by gold nanoparticles. Abstract: Gold nanoparticles (GNP) have emerged as an alternative to biomaterials in biomedical applications. Research has clearly demonstrated the relative safety and low toxicity of these molecules. However, the possible neuroprotective effect of GNP on the central nervous system (CNS) and its relationship with neurological and psychiatric disorders remain unclear. Zebrafish is a reliable model to investigate the impact of ethanol (EtOH) consumption on the CNS, including reward signaling such as the cholinergic neurotransmission system. Here, we investigated whether cotreatment or pretreatment with GNP prevented EtOH-induced changes in acetylcholinesterase activity and oxidative stress in the brain of zebrafish. We exposed adult zebrafish to 2.5 mg·L −1 GNP 1 h prior to EtOH (1% v/v) treatment for 1 h, and cotreated adult zebrafish simultaneously with both substances for 1 h. Pretreatment with GNP did not prevent EtOH-induced increase in the acetylcholinesterase activity, whereas cotreatment with 2.5 mg·L −1 GNP and EtOH protected against this increase. The results also suggested similar protective effect on oxidative stress parameters in the zebrafish pretreated with GNP at 2.5 mg·L −1 . GNP significantly decreased the levels of thiobarbituric acid reactive species and dihydrodichlorofluorescein levels when cotreated with EtOH. GNP also prevented EtOH-induced increase in superoxide dismutase and catalase activities, suggesting a modulatory role of GNP in enzymatic antioxidant defenses. Our results showed that GNP was able to modulate the disruption of cholinergic and oxidative homeostasis in the brain of zebrafish. These findings indicate for the first time that zebrafish is an interesting perspective to investigate nanoparticles against disorders related to alcohol abuse.